Diagnostic impact of myotonic discharges in myofibrillar myopathies. Issue 6 (21st April 2013) - Hanisch, Frank; Kraya, Torsten; Kornhuber, Malte; Zierz, Stephan
<x xml:space="preserve">Abstract</x> Introduction: In patients with myofibrillar myopathies (MFM), myotonic discharges have occasionally been detected by needle electromyography (EMG). Nevertheless, this peculiar type of spontaneous repetitive discharge has not attracted special interest in the genetically heterogeneous MFMs. Methods: EMG features were analyzed in 6 patients with genetically confirmed MFM (n = 1 MYOT, n = 1 DES, n = 2 ZASP, n = 2 FLNC). Results: Fibrillation potentials, positive sharp waves, and myotonic discharges were found in all 6 patients, and complex repetitive discharges were found in 5. Myotonic discharges were detected in approximately 50% of the analyzed muscles independent of the site, including distal (3/6), proximal limb (4/6), and paravertebral muscles (3/6). Clinical myotonia could not be elicited in any patient. Conclusions: Myotonic discharges appear to be part of the electrodiagnostic characteristics of myofibrillar myopathy. Along with other appropriate clinical and histological findings, the presence of myotonic discharges supports the diagnosis of myofibrillar myopathy. Muscle Nerve 47: 845–848, 2013